FAKTOR-FAKTOR YANG MEMENGARUHI STATUS PERFORMA PASIEN TUMOR INTRAKRANIAL DI RSUPN DR. CIPTO MANGUNKUSUMO - Mariana Nur Laila; Rini Andriani; Henry Riyanto Sofyan; Tiara Aninditha (PERDOSNI, 2019)
FACTORS INFLUENCING PERFORMANCE STATUS IN PATIENTS WITH INTRACRANIAL TUMOR AT CIPTO MANGUNKUSUMO GENERAL HOSPITALABSTRACTIntroduction: Patients diagnosed with malignancy have a long course of illness from diagnosis to treatment. Assessment of performance status (PS) is essential to give an overview of therapeutic readiness and patient’s prognosis. Karnofsky Performance Scale is a PS assessment used widely in neurooncology patients. This instrument can assess functional impairment among patients. To this date, clinical factors in admission time that influences KPS in hospitalized intracranial tumor has not been researched.Aim: To get an overview of KPS in hospitalized intracranial patients in Cipto Mangunkusumo General Hospital and to investigate factors that influence.Methods: The design of this research was cohort retrospective. The research was done in Cipto Mangunkusumo General Hospital using secondary data in 2015-2016. The subjects of the research were patients with intracranial tumors. Demographic, clinical status in admission, pathological anatomy, and performance status data were acquired. The data were processed and presented descriptively and analytically. Independent predictors investigated using multivariate logistic regression.Results: There were 68 subjects obtained in this research. As much as 35 (51.5%) subject had primary intracranial tumor. As much as 58 (85.2%) subjects aged <60 years old. As much as 51 (76.5%) subjects had supratentorial tumor. Majority of subjects (70%) had KPS score <70. Subjects with primary tumor had more cranial nerve palsy (p=0.021) and hemiparesis (p=0.038). Decreased consciousness increased the risk of KPS score <70 by 5.2x in the time of admission.Discussion: Majority of subjects had KPS score <70. Decreased consciousness in the time of admission is an independent predictive factor that lowers KPS.Keywords: Karnofsky Performance Scale, intracranial tumor, neurooncology, risk factorsABSTRAKPendahuluan: Pasien keganasan memiliki perjalanan penyakit yang panjang mulai dari diagnosis hingga tata laksana. Kondisi pasien dapat sangat beragam, sehingga penting dilakukan pengkajian status performa untuk memberikan gambaran kesiapan terapi dan prognosisnya. Instrumen yang paling sering digunakan secara standar internasional adalah Karnofsky Performance Scale (KPS). Sejauh ini belum diketahui penggunaan KPS pada pasien tumor intrakranial, mengingat performa pasien yang tidak hanya disebabkan oleh keganasannya, namun juga kecacatan akibat dari lesinya.Tujuan: Mendapatkan gambaran KPS pasien tumor intrakranial serta faktor-faktor yang memengaruhinya.Metode: Penelitian kohort retrospektif terhadap pasien tumor intrakranial yang dirawat di RSUPN Dr. Cipto Mangunkusumo, Jakarta, pada tahun 2015-2016. Dilakukan pencatatan karakteristik demografik pasien, faktor klinis saat admisi, patologi anatomi, dan KPS. Data disajikan secara deskriptif dan analitik, faktor prediktor independen diinvestigasi menggunakan analisis multivariat regresi logistik.Hasil: Didapatkan 68 subjek dalam penelitian ini dengan proporsi tumor primer dan sekunder sebanyak 33 dan 35 orang. Subjek perempuan lebih banyak pada kelompok tumor primer dan lebih sedikit pada tumor sekunder. Mayoritas subjek berusia <60 tahun (85,2%), lokasi tumor di supratentorial (76,5%), dan KPS masuk <70 (69,2%). Subjek dengan penurunan kesadaran saat masuk perawatan akan cenderung memiliki KPS <70 (p=0,005) dibanding faktor-faktor klinis lainnya dengan risiko 5,2x menyebabkan status performa yang rendah tersebut saat admisi.Diskusi: Sebagian besar subjek memiliki nilai KPS <70. Penurunan kesadaran saat admisi merupakan faktor prediktif independen penurunan KPS.Kata kunci: Faktor risiko, Karnofsky Performance Scale, neuroonkologi, tumor intrakranial